Pelatihan Penulisan Ilmiah untuk Pokdarwis DWH Bilebante: Memanfaatkan AI dalam Membangun Arsip Pengetahuan Wisata - Latifah, Annisa; Inne Juni Simamora, Vera; Calista Poluan, Regina (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Bilebante Tourism Village is one of the destinations currently preparing to participate in the Best Tourism Village UNWTO 2026. In this process, the need for systematic and credible documentation has become increasingly important. This community service activity was carried out to address this need, with the primary goal of enhancing the scientific literacy of Pokdarwis DWH Bilebante members through technology-based writing training aimed at producing high-quality tourism knowledge archives. The training was attended by six participants who play a key role in preparing documents for the competition and was conducted in person. The activity methods included a self assessment pre-test, interactive material delivery, discussion sessions, article writing practice, and a self assessment post-test. The materials covered an introduction to scientific articles, paragraph structure, article writing techniques, and the use of ChatGPT for drafting and editing texts. The results of the pre-test, post-test, and article writing practice showed an increase in participants' understanding of scientific writing. The post-test score for the question regarding the ability to write AI-assisted articles increased by 66.6 percent compared to the pre-test. In addition, participants were able to produce complete articles on the theme "Sustainable Tourism Strategies in Bilebante Village," covering social, environmental, and economic dimensions. The quality of the writing demonstrated a good understanding of article structure and effective use of technology to support the writing process. Thus, this activity proved effective in building basic competencies in technology-based scientific writing. In addition to improving understanding, the training also encouraged active community involvement in documentation practices that are relevant and oriented toward the development of a sustainable tourism village.